The introvert's edge : how the quiet and shy can outsell anyone - Pollard, Matthew; Lewis, Derek, 1983- (AMACOM-American Management Association, 2018)
An introvert? Great at sales? YES. Sales is a skill anyone can learn and master -- and introverts are especially good at it once they learn how to leverage their natural strengths. Introverts aren't comfortable with traditional tactics like aggressively pushing a product or talking over a customer's objections. That's the beauty of The Introvert's Edge : it doesn't focus on the sale itself but on a sales system that helps introverts feel sincere instead of sales-y. Powerful and practical, the book reveals how to: Find natural confidence Prepare for every situation Present your value so that customers want to buy Sidestep objections Judge when the customer's ready to buy Ask for the sale -- without asking Continually adapt and improve Profit from a process that doesn't rely on personality Enjoy sales With stories of introverted entrepreneurs, salespeople, and business owners who went from stagnant to success, The Introvert's Edge shows you how to succeed in sales -- without changing who you are.